2018
DOI: 10.1186/s12887-018-1118-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of universal maternal antenatal iron supplementation on neurodevelopment in offspring: a systematic review and meta-analysis

Abstract: BackgroundAlthough antenatal iron supplementation is beneficial to mothers, its impact on the neurodevelopment of offspring is controversial. A systematic review and meta-analysis was undertaken to assess whether routine maternal antenatal iron supplementation confers later neurodevelopmental benefit to offspring.MethodsElectronic databases were searched using MESH terms or key words and identified papers were reviewed by two independent reviewers. The study quality was assessed using the Cochrane risk of bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
(71 reference statements)
0
19
0
Order By: Relevance
“…However, it is not entirely clear that maternal iron supplementation during pregnancy can reverse effects of maternal ID during pregnancy on neurodevelopment [77,78]. Two recent systematic reviews found no evidence that iron supplementation during pregnancy improved neurodevelopment in offspring [76,79]. The specific frequency of ID in the populations studied may have contributed to the absence of a statistically significant effect: benefits may have been confined to patients who were iron deficient or had marginal iron stores at the time of treatment [79,80].…”
Section: Impact Of Id During Pregnancymentioning
confidence: 97%
See 2 more Smart Citations
“…However, it is not entirely clear that maternal iron supplementation during pregnancy can reverse effects of maternal ID during pregnancy on neurodevelopment [77,78]. Two recent systematic reviews found no evidence that iron supplementation during pregnancy improved neurodevelopment in offspring [76,79]. The specific frequency of ID in the populations studied may have contributed to the absence of a statistically significant effect: benefits may have been confined to patients who were iron deficient or had marginal iron stores at the time of treatment [79,80].…”
Section: Impact Of Id During Pregnancymentioning
confidence: 97%
“…Two recent systematic reviews found no evidence that iron supplementation during pregnancy improved neurodevelopment in offspring [76,79]. The specific frequency of ID in the populations studied may have contributed to the absence of a statistically significant effect: benefits may have been confined to patients who were iron deficient or had marginal iron stores at the time of treatment [79,80]. From a standpoint of newborn anemia/iron status, the evidence appears more clear: studies spanning 60 years that consistently support the concept that maternal ID typically does not reduce fetal iron supply.…”
Section: Impact Of Id During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been suggested that ID during pregnancy may not only have effects in early life [5,6,[21][22][23][24] but could also be related to long-term alterations in cognitive, behavior, and social development and poorer school performance during childhood and adolescence [3,12,[25][26][27]. Even so, a review concluded that the influence of maternal iron status during pregnancy on the cognitive function of offspring is inconclusive [13,28,29]. Some reasons for these inconsistencies may be related to methodological issues such as different cognitive assessments or to the time when iron status was assessed during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Although some previous studies have shown that prenatal iron supplementation could improve a child's neuropsychological outcomes [33,34], there is still much controversy and most of the evidence has examined the relationship in small populations, in developing countries, and in the short-term in the first months of life [35][36][37]. A recent meta-analysis concluded that the benefit of routine antenatal iron supplementation for neurodevelopment in offspring was not significant [29]. Moreover, cognitive development can be influenced by multiple factors that must be taken into account, such as obstetrical outcomes, infant breastfeeding, the mother's alcohol and cigarette intake, the mother's intellectual capacity, and the family environment [28,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%